MOOC MAT438/ UiTM
Inverse Trigonometric Functions
Introduction (notation, graph and useful formula)
Evaluating Inverse Trigonometric Functions using Triangle Method
Derivatives of Inverse Trigonometric Functions
Integration of Inverse Trigonometric Functions
MOOC MAT438/ UiTM
Formula (in general) Formula (in Appendix)
න 1 = −1 +
2 − 2
න 2 1 = 1 −1 +
+ 2
න 1 = 1 −1 +
2 − 2
=
=
MOOC MAT438/ UiTM
න 1
3 − 4 2
Write into the
form of 2 and 2
1 1 = 3
න = න
= 2
3 − 4 2 3 2 − 2 2
= 2
=න 1
∙
2 − 2 2 = 2
11 1 −1 1 2
= 2න = 2 + = 2 −1 3 + #
2 − 2
MOOC MAT438/ UiTM
න 2
3 − 4 6
Write into the
form of 2 and 2
2 2 = 3
න = න
= 2 3
3 − 4 6 3 2 − 2 3 2
2 = 6 2
= න 2 − 2 ∙ 6 2
= 6 2
11 1 −1 1 2 3
= 6න = 6 + = 6 −1 3 + #
2 − 2
MOOC MAT438/ UiTM
MOOC MAT438/ UiTM
2 2
න 4 + 9
Write into the
form of 2 and 2
2 2 = 2න 2 3 2 = 3
න 4 + 9 2 2 +
= 2
= 2 2
2
= 2 න 2 + 2 ∙ 2 2 = 2 2
1 = 1 −1 + = 1 −1 2 + #
= න 2 + 2 3 3
MOOC MAT438/ UiTM
න
4 − 2
Write into the
form of 2 and 2
=න 1 = 2
න
=
4 − 2 2 2 − 2 1
=
1 =
= න ∙
2 − 2
=න 1 = −1 + = −1 + #
2 − 2 2
MOOC MAT438/ UiTM
න
2 − 4
1
න = න
2 − 4 2 − 2 2
1
= න
2 − 2
= 1 −1 + = 1 −1 + #
2 2
MOOC MAT438/ UiTM
MOOC MAT438/ UiTM
3 3 The best way is we choose
න 16 + 23
= 3 because
3 = 3 3 3
Write into the
form of 2 and 2
3 3 3 3 = 4
න 16 + 23 = න 4 2 + 3 2
= 3
3 3
= න 2 + 2 ∙ 3 3 3 = 3 3 3
= 3 3 3
11 = 1 1 −1 + = 1 −1 3 + #
= 3 න 2 + 2 3∙ 12 4
MOOC MAT438/ UiTM
න 1 Inverse Trigonometric or
Inverse Hyperbolic, maybe?
8 − 2 + 1 2
න 1 = න 1 Write into the
8 − 2 + 1 2 2 4 − + 1 2 form of 2 and 2
= 2
11 = + 1
=න
2 2 2 − + 1 2
= 1
11 =
=න
2 2 − 2
= 1 −1 + = 1 −1 + 1 + #
2 2 2
MOOC MAT438/ UiTM
MOOC MAT438/ UiTM
න 1 constant Inverse Trigonometric or
Inverse Hyperbolic, maybe?
14 − 12 − 2 2
Write 14 − 12 − 2 2 into
the form of 2 and 2
By using completing
the square method
14 − 12 − 2 2 = −2 2 − 12 + 14 Re-arrange : 2 + +
= −2 2 + 6 − 7
if coefficient of 2 not equal to
positive one, then factorize the
coefficient of 2
= −2 2 + 6 + +3 2 − +3 2 − 7 i) Put + − after the term containing x
2 simplify ii) inside bracket must ( × coeffiecient of x)
= −2 + 3 2 − 16 The first three terms → write
The remaining terms → simplify
= 2 16 − + 3 2
MOOC MAT438/ UiTM
න 1
14 − 12 − 2 2
න 1 = න 1 Write into the
form of 2 and 2
14 − 12 − 2 2 2 16 − + 3 2
= 4
11 = + 3
=න
2 16 − + 3 2
= 1
11 =
=න
2 4 2 − + 3 2
11 = 1 −1 + = 1 −1 + 3 + #
=න 2 2 4
2 2 − 2
MOOC MAT438/ UiTM
MOOC MAT438/ UiTM
constant Inverse Trigonometric or
Inverse Hyperbolic, maybe?
න 2 2 − 8 + 26
Write 2 2 − 8 + 26
into the form of 2 and 2 By using completing
the square method
2 2 − 8 + 26 = 2 2 − 4 + 13 Re-arrange : 2 + +
= 2 2 − 4 + −2 2 − −2 2 + 13 if coefficient of 2 not equal to
positive one, then factorize the
coefficient of 2
2 simplify i) Put + − after the term containing x
= 2 − 2 2 + 9 ii) inside bracket must ( × coeffiecient of x)
The first three terms → write
= 2 − 2 2 + 3 2 The remaining terms → simplify
MOOC MAT438/ UiTM
න 2 2 − 8 + 26
=න 1 Write into the
න 2 2 − 8 + 26 2 form of 2 and 2
− 2 2 + 3 2
= 3
11 = − 2
= 2 න − 2 2 + 3 2
11 = 1
= 2 න 2 + 2 =
= 1 ∙ 1 −1 + = 1 −1 − 2 + #
2 6 3
MOOC MAT438/ UiTM
MOOC MAT438/ UiTM